Parental emotion and pain control behaviour when faced with child's pain: the emotion regulatory role of parental pain-related attention-set shifting and heart rate variability. Issue 2 (February 2019) - Vervoort, Tine; Karos, Kai; Johnson, Dan; Sütterlin, Stefan; Van Ryckeghem, Dimitri
Abstract : Abstract: This study investigated the moderating role of parental pain-related attention-set shifting and heart rate variability (HRV) for parental distress and pain control behaviour when faced with their child's pain. Participants were 54 schoolchildren and one of their parents. Parental HRV was assessed at study commencement followed by a cued-switching task indexing parental ability to flexibly shift attention between pain-related and neutral attentional sets. In a subsequent phase, parents observed their child perform a cold-pressor task [CPT], allowing for assessment of parental pain control behavior (indexed by latency to stop their child's CPT performance) and parental distress—assessed through self-report following observation of child CPT performance. Findings indicated that parental facilitated attentional shifting (ie, engage) towards a pain-related attentional set contributed to higher levels of pain control behaviour when faced with increasing levels of child facial display of pain. Pain control behaviour among parents who demonstrated impeded attentional shifting to a pain-related attentional set was equally pronounced regardless of low or high levels of child pain expression. Parental ability to shift attention away (ie, disengage) from a pain-related set to a neutral set did not impact findings. Results further indicated that although high levels of parental HRV buffer the impact of child facial pain display on parental emotional distress and pain control behaviour, low levels of HRV constitute a risk factor for higher levels of parental distress and pain control behaviour when faced with increased child facial pain display. Theoretical/clinical implications and further research directions are discussed. Abstract : Parental pain-related attention-set shifting and heart rate variability impacts parental distress and pain control behaviour when faced with their child's pain.